"Uradome" treatment for prevention of snow damage and terrain parameters of moso bamboo (Phyllostachys pubescens) forest in Tsuruoka, Yamagata Prefecture. (17th February 2019) - Furusawa, Yuka; Takahashi, Koetsu; Ashitani, Tatsuya
ABSTRACT: Moso bamboo ( Phyllostachys pubescens ) is cultivated for edible bamboo shoot production in Japan. Yamagata Prefecture is located in a heavy-snowfall region at the northern limit of the cultivated area. However, snow damage to bamboo culms occurs every year and decreases bamboo shoot production. "Uradome" is a treatment that involves cutting off the upper portion of the new culms when the bamboo shoot is almost fully grown. We studied the effect of "Uradome" implementation on incidence of snow damage to bamboo culms. In addition, we investigated terrain characteristics of bamboo forest at sites where snow damage occurred. As a result, the higher the degree of "Uradome" was, the lower the damage rate was. Furthermore, the results revealed that implementation of "Uradome" prevents snow damage to culms. It is considered that snow damage may be prevented by rendering the culm shape straight as a result of "Uradome". The results also indicated that snow damage is more likely to occur on steep slopes. Factors that influence the incidence and severity of snow damage are considered to differ between Japan and other countries. Therefore, it is desirable to adopt preventative measures against snow damage, such as the "Uradome" method, irrespective of the local climate and terrain.